Association of non-contrast CT markers with long-term functional outcome in deep intracerebral hemorrhage - Kölbl, Kathrin; Hock, Stefan W.; Xu, Mingming; Sembill, Jochen A.; Mrochen, Anne; Balk, Stefanie; Lang, Stefan; Volbers, Bastian; Engelhorn, Tobias; Kallmünzer, Bernd; Kuramatsu, Joji B. (Frontiers in Neurology, 2024)
Hematoma expansion (HE) is the most important therapeutic target during acute care of patients with intracerebral hemorrhage (ICH). Imaging biomarkers such as non-contrast CT (NCCT) markers have been associated with increasing risk for HE. The aim of the present study was to evaluate the influence of NCCT markers with functional long-term outcome and with HE in patients with deep (basal ganglia, thalamus) ICH who represent an important subgroup of patients at highest risk for functional deterioration with HE due to the eloquence of the affected brain region.From our prospective institutional data base all patients maximally treated with deep ICH were included and retrospectively analyzed. NCCT markers were recorded at diagnostic imaging, ICH volume characteristics were volumetrically evaluated, and all patients received follow-up imaging within 0-48 hours. We explored associations of NCCT makers with unfavorable functional outcome, defined as modified Rankin-Scale 4-6, after 12 months and with HE. Bias and confounding were addressed by multivariable regression modelling.